2015
DOI: 10.5121/ijcsit.2015.7409
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Technology Acceptance Model to Understand Social Networking Sites (SNS) Usage: Impact of Perceived Social Capital

Abstract: This study examines the individuals' participation intentions and behaviour on Social Networking Sites (SNSs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Based on the TRA, Davis (1989) put forward the Technology Acceptance Model (TAM), which is used for forecasting the possibility of a person accepting and using an information system. TAM is remarkable tool for making such predictions, and more and more scholars apply its theoretical framework to different fields, such as health information seeking (Lemire et al, 2008;Liang, Xue, & Chase, 2011) and social networking (Al-Ghaith, 2015). The Model (Figure 3) proposes two determinants: perceived usefulness (e.g.…”
Section: Research Modelmentioning
confidence: 99%
“…Based on the TRA, Davis (1989) put forward the Technology Acceptance Model (TAM), which is used for forecasting the possibility of a person accepting and using an information system. TAM is remarkable tool for making such predictions, and more and more scholars apply its theoretical framework to different fields, such as health information seeking (Lemire et al, 2008;Liang, Xue, & Chase, 2011) and social networking (Al-Ghaith, 2015). The Model (Figure 3) proposes two determinants: perceived usefulness (e.g.…”
Section: Research Modelmentioning
confidence: 99%
“…As per previous studies, PEoU has a significant and positive effect on PU. The direct relationship between PEoU and PU was reported in several studies, for example, internet acceptance by undergraduate students in the USA (Yi & Hwang, 2003), SNS acceptance (Leng et al, 2011;Nasri & Charfeddine, 2012;Al-Ghaith, 2015), personal digital assistance for adults in Germany (Arning & Ziefle, 2007), acceptance of short message service (Lu, Deng, & Wang, 2010), and use of mobile-based ICTs (Meso et al, 2005). The following hypotheses have been proposed based on the above studies: Hypothesis-1: PEoU has significant positive influence on PU of social media.…”
Section: Theoretical Frameworkmentioning
confidence: 76%
“…It has been extensively used for studying social media acceptance and use, for instance, on Social Networking Sites (SNS) (Leng, Lada, Muhammad, Ibrahim, & Amboala, 2011;Sago, 2013;Al-Ghaith, Sanzogni, & Sandhu, 2010;Al Ghaith, 2015;Nah & Saxton, 2012;Rauniar, Rawski, Yang, & Johnson, 2014;Nasri & Charfeddine, 2012). Figure 1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Social networking sites are also used to contact colleagues, friends and relatives. However, with the advances in social and technological platforms, people have also started interacting with strangers through social networking sites [4,5,6,7,8,9,10,11,12,13,14]. Out of these, strangers' research has also shown that males have a greater tendency to flame than female participants [4].…”
Section: Flaming In Chatting Applications and Flame Detector Toolmentioning
confidence: 99%